Antecedents and Outcomes of Enrichment Among Working Family Caregivers of People With Dementia: A Longitudinal Analysis. (25th October 2020) - Morimoto, Hiroshi; Takebayashi, Yoshitake
Abstract: Objectives: Despite evidence of negative aspects of the work–caregiving interface (e.g., work–family conflict) among family caregivers of people with dementia (PWD), little is known about the positive aspects (e.g., enrichment). We examined antecedents and outcomes of family-to-work enrichment (FWE) and work-to-family enrichment (WFE) among working family caregivers of PWD. In terms of antecedents, we investigated whether factors that alleviated work–family conflict increased enrichment. Method: We conducted a 3-wave 6-month-interval longitudinal online survey of Japanese working family caregivers of PWD ( N = 747). We examined the mediational effects of WFE and FWE on associations between participants' work resources (job control, supervisor support, co-worker support, and organizational support) and caregiving support and their well-being (psychological distress and quality of life). We also examined the moderating effect of caregiving self-efficacy on the relationships between caregiving support/caregiving demands and FWE. Results: Our longitudinal analysis confirmed supervisor support had a positive effect on WFE. FWE had no significant longitudinal mediating effect on the association between caregiving support and well-being, and self-efficacy had no longitudinal moderating effect on FWE. Discussion: Supervisor support is important for WFE, but greater enrichment does not necessarily improve family caregiver well-being. Caregiving experience (i.e., caregiving demands and caregiving support) has little effect on the work–caregiving interface. Policy makers should focus on supporting companies to create family-friendly work environments. More research is needed on factors that increase FWE and moderate the relationship between enrichment and working family caregivers' well-being.